2005
DOI: 10.4314/jasem.v9i2.17288
|View full text |Cite
|
Sign up to set email alerts
|

Using GIS to understand the environmental chemistry of manganese contaminated soils, Kgwakgwe area, Botswana

Abstract: ABSTRACT:This study aimed at establishing the spatial distribution of manganese (Mn) and iron (Fe) within

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…By applying clustering techniques, however, it was shown that most of the silt loam and sandy loam belonged to clusters 1, 2 and 5. In a related study [2], it was demonstrated that the soil samples from the south and particularly those closer to mine workings of the study area had higher concentrations of Mn compared to those from the northwest; a fact which was further substantiated by determining the spatial distribution of Mn in the vegetation cover of the area [3]. Possible chemical reactions such as adherence of Mn particles on the surface area of clayey particles, and isomophous substitution of Mn ions in the lattice structures of the clay minerals present at Kgwakgwe [23], leaching, hydrolysis among others, could lend supporting evidence of increase in Mn concentrations and alteration of particle sizes of soil particles within the study area and their distributions.…”
Section: Environmental Implications and Land Usementioning
confidence: 98%
See 2 more Smart Citations
“…By applying clustering techniques, however, it was shown that most of the silt loam and sandy loam belonged to clusters 1, 2 and 5. In a related study [2], it was demonstrated that the soil samples from the south and particularly those closer to mine workings of the study area had higher concentrations of Mn compared to those from the northwest; a fact which was further substantiated by determining the spatial distribution of Mn in the vegetation cover of the area [3]. Possible chemical reactions such as adherence of Mn particles on the surface area of clayey particles, and isomophous substitution of Mn ions in the lattice structures of the clay minerals present at Kgwakgwe [23], leaching, hydrolysis among others, could lend supporting evidence of increase in Mn concentrations and alteration of particle sizes of soil particles within the study area and their distributions.…”
Section: Environmental Implications and Land Usementioning
confidence: 98%
“…The silt loam soils in the northern part of the study area may have been altered to silt and sandy loam soils due to changes in particle size as a result of increase in Mn and Fe concentrations in the soils. Furthermore, the soils within the study area are currently contaminated with both Mn and Fe [2,3]. The predominance of these ions in the soils makes the land generally unsuitable for commercial agriculture, though some form of subsistence agriculture (classified as other agricultural land) could be considered.…”
Section: Environmental Implications and Land Usementioning
confidence: 99%
See 1 more Smart Citation
“…The high turbidity is because of discharge of effluents during the sand mining process into the streams. High turbidity is not good for human consumption [12][13][14][15][16]. Typhoid has accounted for (28%) by 20 respondents, malaria 17(24.3%), diarrhea 9(12.9%), cholera 8(11.42), guinea worm (15.7%) and dysentery 5(7.1%) (Table 3).…”
Section: Health Implications Of the Surface Water Qualitymentioning
confidence: 99%
“…GIS techniques have been applied to understand the distribution of different parameters in physical environments (Ekosse et. al, 2002;Zhang & Lalor, 2003;Ekosse & Fouche, 2005a, 2005b, 2005cEkosse et al, 2005). To the authors' knowledge, no case is documented where this technique has been used to determine the spatial distribution patterns of BSP, CEC, pH (water) and EC in soils situated close to an abandoned manganese mine.…”
Section: July 2008mentioning
confidence: 99%